Global Patterns and Drivers of Litter Decomposition Under Nitrogen Enrichment: A Meta-Analysis - Su, Yuan; Ma, Xiaofei; Gong, Yanming; Ahmed, Zeeshan; Han, Wenxuan; Li, Kaihui; Liu, Xuejun (Frontiers in Forests and Global Change, 2022)
Nitrogen (N) enrichment has substantially altered patterns of terrestrial litter decomposition, with positive, neutral, and negative effects. However, the general response patterns and drivers of litter decomposition to N enrichment rates are poorly understood, and how litter decomposition has changed under the N enrichment rate, especially in different ecosystems, still requires further study. We reviewed 118 published papers dealing with litter mass remaining after N enrichment to assess the influences of various environmental and experimental factors on the relationships between N enrichment and litter decomposition in grasslands, forests, and wetland ecosystems. The results indicated that N enrichment had an insignificant effect on litter decomposition globally. However, the effects varied greatly among ecosystem types, with an increase in litter decomposition of 3.91% in grasslands and 1.82% in wetlands and a decrease of 1.23% in forests. When forests were subdivided into plantations, primary, and secondary forests, the results showed that N enrichment significantly slowed litter decomposition rate by 2.96% in plantations but had no significant influence in primary and secondary forests. However, litter decomposition was significantly influenced by the level of N addition in plantations and secondary forests, with an increase in litter mass loss at low N addition (50 kg N ha–1 year–1) and a decrease in litter mass loss at high N addition (>50 kg N ha–1 year–1). The magnitude and direction of the N effect are affected by experimental and environmental factors. Specifically, mixed N enrichment (for example, urea and glycine) exerted a stronger effect on litter decomposition compared with an N fertilizer alone. Our findings indicated the different effects of N on litter decomposition in forests and grasslands and knowledge which will greatly advance our ability to accurately evaluate and predict global C cycling under increased N deposition, which should improve future models of global biogeochemical cycling.